Chaostheorie und Literaturwissenschaft - Wozonig, Karin S. (Studien Verlag, 2008)
This book presents the development and present status of adaptions of chaos theory for literary studies. Furthermore the integration of these methodological approaches into a discipline that is oriented towards cultural studies is demonstrated. The publication consists of four parts. The first part of the work deals with the issues created through questions posed by historical philosophy and historiography. It discusses how reflections on linear time, as well as on the description and explanation of sequences, circularity and synchronicities lead to an increased complexity in the semanticts of time in the notion of the objects analized. It also discusses the integration of discourses from other disciplines into literary history. It is demonstrated that both aspects - increased complexity and supplementary discourses - are highly influential in hermeneutical literary studies. The second part deals with changes in the notion of time in the modern and so-called post-modern era. It focuses especially on non-linearity, the increasing importance of historical time in the natural sciences and on the effect of this tendency on the analysis of highly complex structures outside of the natural sciences. In the third part of the publication concrete examples of the adaption of chaos theory for literary studies are examined - especially their epistemological interest, their position within the framework of the discipline and their interdisciplinary potential. This part elucidates the potential of focusing on the literary text and its particularities under the premises of chaos theory and how such an interdisciplinary approach helps to bridge the cap between the natural sciences and the humanities. In the final part of the publication the social and cultural relevance of historical knowledge as a frame of reference in times of increasing (temporal and social) complexity is examined. With reference to the explanatory power of hermeneutical procedures "chaostheoretical literary studies" are proposed as a working hypothesis. The approach is intended as a model which can be integrated into cultural analysis and not provides descriptions and explanations for highly complex literary texts, hypertexts and virtual realities, but also regards scientific and technical production and distribution of knowledge as an important part of culture and thus integrates it into its analysis.